Multiwavelength Observations of the AGN 1ES 0414+009 with VERITAS, Fermi-LAT, Swift-XRT, and MDM - Aliu, E. (2012)
We present observations of the BL Lac object 1ES 0414+009 in the E > 200 GeV gamma-ray band by the VERITAS array of Cherenkov telescopes. 1ES 0414+009 was observed by VERITAS between 2008 January and 2011 February, resulting in 56.2 hr of good quality pointed observations. These observations resulted in a detection of 822 events from the source corresponding to a statistical significance of 6.4 standard deviations (6.4sigma) above the background. The source flux, showing no evidence for variability, is measured as (5.2 ± 1.1stat ± 2.6sys)× 10^-12 photons cm^-2 s^-1 above 200 GeV, equivalent to approximately 2% of the Crab Nebula flux above this energy. The differential photon spectrum from 230 GeV to 850 GeV is well fit by a power law with a photon index of Gamma = 3.4 ± 0.5stat ± 0.3sys and a flux normalization of (1.6 ± 0.3stat ± 0.8sys) × 10^-11 photons cm^-2 s^-1 at 300 GeV. We also present multiwavelength results taken in the optical (MDM), x-ray (Swift-XRT), and GeV (Fermi-LAT) bands and use these results to construct a broadband spectral energy distribution (SED). Modeling of this SED indicates that homogenous one-zone leptonic scenarios are not adequate to describe emission from the system, with a lepto-hadronic model providing a better fit to the data.